2013
DOI: 10.1128/jb.00726-13
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa AlgR Phosphorylation Modulates Rhamnolipid Production and Motility

Abstract: bAlgR is a key Pseudomonas aeruginosa transcriptional response regulator required for virulence. AlgR activates alginate production and twitching motility but represses the Rhl quorum-sensing (QS) system, including rhamnolipid production. The role of AlgR phosphorylation is enigmatic, since phosphorylated AlgR (AlgR-P) is required for twitching motility through the fimU promoter but is not required for the activation of alginate production. In order to examine the role of AlgR phosphorylation in vivo, a PAO1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 90 publications
(131 reference statements)
1
50
1
Order By: Relevance
“…In addition, it has also recently been suggested that BfmRS is involved the development of virulence during bacterial adaptation to the CF lung (43,44). Interestingly, AlgR (another key P. aeruginosa transcriptional response regulator) also appears to play an essential role in bacterial virulence and motility (45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has also recently been suggested that BfmRS is involved the development of virulence during bacterial adaptation to the CF lung (43,44). Interestingly, AlgR (another key P. aeruginosa transcriptional response regulator) also appears to play an essential role in bacterial virulence and motility (45).…”
Section: Discussionmentioning
confidence: 99%
“…One of the transcriptional regulators that controls alginate overproduction as well as other virulence factors, such as type IV pili, the type III secretion system, and rhamnolipid and cyanide production, is the response regulator AlgR (58). The proposed histidine kinase for AlgR, AlgZ (FimS), is required for type IV pili (25) function but also modulates alginate and rhamnolipid production by two-to threefold (24,27). Consequently, determining the transcriptional regulators that control the AlgZR two-component regulatory system provides insights into the functions of many different P. aeruginosa virulence determinants.…”
Section: Figmentioning
confidence: 99%
“…Because AlgR is part of a two-component system that is important for both acute and chronic infections (19,32), it was necessary to address the mechanism for AlgR activation of rsmA in order to create a framework to understand how AlgR regulation of rsmA might impact virulence gene expression. AlgR binds a consensus sequence CCGTTCGTC (21,48,49), and phosphorylation is thought to enable AlgR to bind potential binding sites that deviate from this consensus, such as the sites found in the fimU promoter (32,47). However, the rsmA promoter deviates from the AlgR-binding consensus, and AlgR phosphorylation was not required for rsmA expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of acute infections, AlgR activates the fimU operon, enabling the production of T4P (19,21,47). In chronic infections, AlgR, AlgU, and other transcriptional regulators activate the production of alginate (22,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%